Bcl‐2 level as a biomarker for 13q14 deletion in CLL. Issue 4 (14th May 2013) - Degheidy, Heba A.; Gadalla, Shahinaz M.; Farooqui, Mohammed Z. H.; Abbasi, Fatima; Arthur, Diane C.; Bauer, Steven R.; Wilson, Wyndham H.; Wiestner, Adrian; Stetler‐Stevenson, M. A.; Marti, Gerald E.
Abstract : Background: Deletion 13q14.3 is the most common cytogenetic abnormality in chronic lymphocytic leukemia (CLL). Previously it was reported that miR‐15/16 is the target of 13q14 deletions and plays a tumor suppressor role by suppressing Bcl‐2. Therefore, Bcl‐2 expression was examined more closely to determine whether it would predict 13q14 deletion status. Methods: A multi‐color flow panel consisting of anti‐Bcl‐2/anti‐lambda/anti‐kappa/CD19/CD5/CD3/CD20 was performed. The ability of Bcl‐2 to predict 13q14 deletion was tested using the conventional Bcl‐2 index (c‐index): mean fluorescence intensity (MFI) of CLL clone/MFI of residual T cells. Fifty‐four untreated CLL/MBL patients were studied. Bimodal Bcl‐2 expression was evaluated to test the ability of Bcl‐2 to detect intraclonal heterogeneity. Other CLL prognostic markers including CD38, CD49d, CD26, and CD69 were evaluated. FISH was performed on selected sorted populations. Results: The Bcl‐2 c‐index strongly predicts del13q14 P < 0.0001. A statistically significant association was observed between the percentage of cells carrying the deletion and the level of Bcl‐2 expression P < 0.05. Cells sorted based on Bcl‐2 expression showed enrichment of both hemizygous and homozygous del 13q14 cells. Also, we observed that an alteration in Bcl‐2 level over time predicts changes in 13q14 deletion status. And a statistically significant correlation between the bimodal pattern of CD69 expression and the presence of 13q14 deletion was found P < 0.0001. Conclusion: Bcl‐2 expression using the c‐index strongly predicts 13q14 deletion and can be used to distinguish homozygous, heterozygous, and diploid CLL clonal cells. Further systematic studies of this biomarker are needed for confirmation and expansion of these findings. Published 2013 Wiley‐Periodicals, Inc.